2017
DOI: 10.1107/s2053229616011980
|View full text |Cite
|
Sign up to set email alerts
|

Structure and physicochemical characterization of a naproxen–picolinamide cocrystal

Abstract: The crystal structure is reported of a new 1:1 cocrystal of naproxen with picolinamide, and the pharmaceutically relevant properties are investigated. An NMR crystallography approach is used to distinguish between two crystallographically unique COOH–CONH hydrogen-bonded dimers and to confirm the location of the H atoms in the two dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
4
25
0
1
Order By: Relevance
“…It should be noted that for processes involving chiral systems the dependence on concentration is typical and is usually explained by the tendency of chiral compounds to form associates . It is known that naphthalene and its substituted derivatives, as well as NPX, form dimers and excimers in the solid state and in solution . In particular, the NPX–NPX dyad excimer is described herein .…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…It should be noted that for processes involving chiral systems the dependence on concentration is typical and is usually explained by the tendency of chiral compounds to form associates . It is known that naphthalene and its substituted derivatives, as well as NPX, form dimers and excimers in the solid state and in solution . In particular, the NPX–NPX dyad excimer is described herein .…”
Section: Introductionmentioning
confidence: 66%
“…Heterodimers (cocrystals) of NPX with different organic compounds and biomolecules (nicotinamide, isonicotinamide, picolinamide, alanine, tyrosine, tryptophan (Trp), etc.) have also been reported in the literature, and X‐ray and solid‐state NMR spectroscopy studies have shown that these associates are formed through hydrogen bonding of NPX carboxylic groups with NH and OH groups of the partner molecules …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…There are reference data on the formation of dimers and excimers of substituted naphthalenes and NPX in solution . The association of NPX with biomolecules was also recorded by means of solid‐state NMR spectroscopy and XRD, and shown to occur due to the formation of hydrogen bonds between the carboxyl group of NPX and the NH and OH protons of biomolecules (amino acids and others) …”
Section: Relationship Between Spin Selectivity and Dyad Associationmentioning
confidence: 99%